L’intégration politique des islamistes tunisiens via les syndicats - Anna Grasso (L’Année du Maghreb)
In Tunisia, following the January 14th 2011 «revolution», the Ennahdha party has established itself as a major player in Tunisian politics. The scope of this publication is to examine the evolution of this party’s relations with the Tunisian trade union field before and after the revolution. In order to do so, we studied the relationship between the Islamist party and two trade unions, as well as the imam unions which are associated to them. These two trade unions are: the Tunisian General Labour Union (UGTT) - the main trade union of the country, created in 1946 - and the Tunisian Labour Organisation (OTT) – a trade union created in 2013, close to the Islamist ideology. This analysis reveals the difficulties and the causes for Ennahdha’s failure to have a real influence in the Tunisian trade union field.